Preparing nurse educators for NMC standards for student supervision and assessment: the impact 4 years on. (9th February 2023) - Whaley, Viki; Hay, Jonathan; Knight, Kate H.
Abstract : Four years on from its launch in 2018 (at the time of writing), the authors provide an up-to-date efficacy assessment of the ongoing implementation of the Nursing and Midwifery Council's Future Nurse: Standards of Proficiency for Registered Nurses (NMC) (2018a) . Although these standards have comprehensively transformed the mentorship practices of nursing education courses within higher education, this article provides the first attempt to gauge and synthesise attitudes towards their implementation. Presenting the results of an evaluative survey that collates educators' current views on the implementation of these NMC standards, the authors detail and analyse the past and continuing impacts of this paradigm shift on staff, students, and practice. The findings contribute to the nascent body of knowledge, primarily clustering around four interlinked themes: slow acclimatisation to new models of assessment and supervision; variation in levels of preparation; prohibitive workloads; and role conflict. The authors conclude by providing a recommendation that more robust training resources around the NMC's standards are implemented nationally, in order to provide consistency of delivery by educators across the sector.